Portugal 1890-1990. - Musée de la Photographie, Mont-sur-Marchienne; Provinciaal Museum voor Fotografie, Antwerpen; Europalia Portugal, 1991 (Brussel : Europalia International, 1991)
Benoliel, Joshua ; Calvet, Carlos ; Afonso Dias, Carlos ; Guerra, Jorge ; Castello Lopes, Gerard ; Martins, António José ; Martins, Costa ; Palla, Vitor ; Sena da Silvz, António ; Arentz, Dick ; Bianchi, Lynn ; Boubat, Edouard ; Bubley, Esther ; Callahan, Harry ; Cartier-Bresson, Henri ; Delano, Jack ; Evans, Walker ; Fink, Peter ; Frankel, Godfrey ; etc.
Portugal 1890-1990, Musée de la Photographie, Mont-sur-Marchienne, 21.9. - 24.11.1991 ; Provinciaal Museum voor Fotografie, Antwerpen, 28.9. - 17.11.1991
boek
Keywords: Portugal